Poverty, AIDS and Hunger - Conroy, A. author. aut Link
XXII, 251 p.
Keywords: Using the experiences of Malawi, one of the poorest countries on the African continent, to illustrate both the challenges that poverty creates, and the opportunities for change that exist. Poverty, AIDS and Hunger outlines an easily-replicable model, at modest cost, that could lift people quickly out of poverty, with sustainable benefits.